Observatório da Acessibilidade da Web Brasileira - Pardini, Rafael; Bárbara, João; Scheid, Henrique; Pereira, Adriano C. M.; Meira Jr., Wagner; Ferraz, Reinaldo; Rocha, Beatriz (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2021: Anais Estendidos do XXVII Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2021.17615, 2021)
The World Wide Web emerged more than three decades ago, and even after all this time, accessibility is still challenging and a major obstacle for it to be universal and inclusive. Despite W3C eff orts to standardize and publish best practices towards a more accessible Web, we still lack methodologies and tools to collect Web content, measure and assess accessibility at large scale. In this work, we describe the Observatório da Acessibilidade Brasileira, a tool that supports accessibility assessment, aggregates global indicators and provides recommendations for improving accessibility on websites. The current version complies with eMAG accessibility standards and extends and integrates existing free software. We validate and demonstrate the effectiveness of the tool by assessing the accessibility of the Brazilian government websites. The tool roadmap includes adding new accessibility compliance analyses, improving data visualization and enriching website seed.